A framework for an online forum for a writing course. - Mei-Yuit , Chan; Ngee-Thai , Yap (2008)
The bane of teaching writing is that there is a scarcity of CALL (computer-assisted language learning) courseware that can effectively teach writing. Conventional CALL systems are unable to interact realistically and meaningfully with students and to provide the motivation for students to write. The success of e-Learning 2.0 that creatively applies technologies for social networking to education has pointed out a new direction for CALL. Based on insights from e-Learning 2.0, an online forum was developed and implemented as the CALL component of a writing course for ESL English as a second language) learners in a university in Malaysia. The online forum project was conceptualised with the specific aim of helping to achieve the objectives of the classroom-based writing course it complements. With proper planning and implementation, the forum technology can be successfully utilised to complement writing instruction. This paper presents the framework that was used to guide the designing of the forum. It describes the five basic components of the framework, that are course objectives, the model adopted for the forum, pedagogical considerations, control, and teacher role.